Microminerals in blood in four bovine genotypes in the Ecuadorian Amazonia - Quinteros, Roberto (2017)
The objective of this work was to evaluate the concentration of macro-minerals in blood of dairy cows of four dairy genotypes under free grazing conditions in the province of Napo, Ecuador. Thirty-six first-calving Bos indicus crosses were evaluated. Crosses were with Gyr, Brown Swiss, Jersey and Sahiwal. Blood samples were taken on days 60 and 21 before calving, at calving, and at 30, 60 and 90 days post-calving. Plasma values of calcium (Ca2+), phosphorus (P), magnesium (Mg) potassium (K+), sodium (Na+) and chlorine (Cl) were determined. None of the mineral concentration values showed significant differences between crosses and the values were among the reference values for dairy cows.